Contextual influence of highly valued rewards and penalties on delay decisions in children with ADHD - Marx, Ivo; Pieper, Juliane; Berger, Christoph; Häßler, Frank; Herpertz, Sabine (Journal of behavior therapy and experimental psychiatry, 2011)
In this study, we examined the influence of both reward and penalty on delay decisions in subjects with ADHD. Eighteen 6- to 13-year-old boys with ADHD (combined or hyperactive-impulsive subtype) along with age- and IQ-matched control participants performed a memory game. If the children were successful at the game, they could choose between a small immediate reward (one white chip in exchange for 5 s of waiting) or a large delayed reward (two white chips in exchange for 60 s of waiting). If they failed, they could choose between a large immediate penalty (two black chips in exchange for 5 s of waiting) or a small delayed penalty (one black chip in exchange for 60 s of waiting). Subsequent to task completion, white chips were exchanged for video time and black chips were exchanged with completion of a written task. All of the participants, regardless of ADHD diagnosis, were motivated to complete the task and chose the delayed alternative most often. We conclude that under highly motivating conditions, children with ADHD are not more delay averse than children from the control group with respect to anticipation of reward and penalty.